Pengaruh Penggunaan KNO3 dan Pupuk Kandang Sapi Terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq) Fase Pre - Nursery - Cindy Yolanda; Ida Zulfida; Dora Silvia Dewi (JURNAL AGROPLASMA, 2023)
Oil Palm (Elaeis guinensis Jacq.) belongs to the Arecaceae family. Indonesia contributes 48% of international CPO production (Nasamsir and Romadoni, 2020). Palm oil is a raw material for producing vegetable oil which has many benefits as edible oil, industrial oil and biodiesel (biofuel). This research will be carried out from April 2023 to June 2023, at the Experimental Field of the Faculty of Agriculture, Indonesian Community Development University, Medan. On Jl. Market village hall 12 Marendal II, Patumbak District, Deli Serdang Regency. This research was conducted using a factorial randomized block design (RBD) which consisted of two factors, namely: Factor I was KNO3 administration which consisted of 3 levels, namely: K0 = without KNO3 administration, K1 = 30 g/polybag KNO3, K2 = 60g/polybag KNO3. Factor II was the application of Cattle Manure which consisted of 3 treatment levels, namely: C0 = Without Giving Cattle Manure, C1 = 100g/polybag of Cattle Manure, and C2 = 200g/polybag of Cow Manure. The results showed that the single effect of giving cow manure had an effect on increasing plant height (at 3 weeks old, 6 weeks old, and 9 weeks old), number of leaves (at 3 weeks old), leaf width (at 3 weeks old, 6 weeks old, and 9 weeks old), and leaf diameter (at 3 weeks old and 6 weeks old). Single effect Urea administration had an effect on increasing the growth of the number of leaves at the age of 3mst but had no significant effect on plant height, leaf width and stem diameter. The interaction effect of KNO3 fertilizer and cow manure had no effect on plant height, number of leaves, leaf width, and stem diameter.